Knowledge attitude and perception regarding oral health in Medical and Nursing students-A Questionnaire Based Survey - Tungariya, Krishna; Kamala, K. A.; S. Sankethguddad, S. Sankethguddad; SR, Ashwinirani; Mahajan, Madhura (Journal of Neonatal Surgery, 2025)
Background: Oral health is an essential yet often overlooked component of overall health. Despite growing evidence linking poor oral health to systemic conditions such as cardiovascular disease, diabetes, and cognitive decline, awareness and integration of oral health into general healthcare remain limited. Medical and nursing students, as future healthcare providers, play a critical role in addressing this gap through interprofessional collaboration and patient education. Aim: To assess the knowledge, attitude, and perception regarding oral health and its systemic implications among medical and nursing students. Materials and Methods: A cross-sectional questionnaire-based survey was conducted among 80 medical and nursing students aged 18–30 years. The study was approved by the Krishna Vishwa Vidyapeeth Institutional Clinical Research Ethics Committee (Protocol No. 082/2024-2025). A 23-item structured questionnaire was distributed via Google Forms, covering four key domains: general information, oral health status, awareness, and perceived oral-systemic health connections. Data were analyzed using SPSS version 16.0 with descriptive statistics and Chi-square tests (p < 0.05 considered significant). Results: 66.67% of participants visited the dentist only when problems occurred, while 93.33% agreed that maintaining good oral hygiene is vital. 73.08% had not been informed by a healthcare provider about oral-systemic health links. Attitudinal differences were observed across gender, occupation, and geographic background. Nursing students demonstrated slightly lower awareness levels compared to medical students. Conclusion: Although students acknowledge the importance of oral hygiene, there exists a significant gap in awareness of its systemic implications. Integrating oral health education into medical and nursing curricula is essential to promote comprehensive, patient-centered care.